What should churches do? Evangelical perspectives on church involvement in an era of community health. Issue 1 (1st January 2017) - Franz, Berkeley; Skinner, Daniel; Kelleher, Kelly
Abstract: Health disparities in the US pose a significant challenge to scholars, providers, and community activists. An ongoing transition to population health shifts the focus away from individual health outcomes to the prevention of disease and the wellbeing of communities. This approach, however, requires developing partnerships with communities to enact appropriate interventions. In this article, Evangelical churches, an important community institution in the US, are considered potential stakeholders in future health initiatives. We present qualitative findings from 29 Christian Evangelical Protestants, on how Evangelicals themselves view their role in caring for the health of their communities. Our findings suggest a need for: better understanding of the boundaries between (a) domains that require elite expertise, (b) domains in which non-elites such as pastors and parishioners can play a role, and (c) domains in which elites within churches might play an important role through volunteer efforts.